1991
DOI: 10.1159/000200678
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Receptors for Bombesin, Gastrin and Cholecystokinin in Pancreatic Secretion and Growth

Abstract: The effects of bombesin, gastrin and cholecystokinin (CCK) on amylase secretion from the isolated rat pancreatic acini and on DNA synthesis (as biochemical indicator of trophic action) in the pancreas have been examined in 48-hour fasted and 16-hour refed rats with and without administration of specific receptor antagonists for bombesin, gastrin and CCK. Studies on the isolated rat acini revealed that bombesin, gastrin and CCK-8 all showed the same efficacy in their ability to stimulate amylase release. RC-309… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Antagonist RC-3095 was highly active in vivo in rats, dogs, and cats in abolishing gastric and pancreatic secretion [45]. Potential oncological application of antagonist RC-3095 was revealed in our studies on pancreatic, colon, and mammary cancers, in which the administration of RC-3095 from Alzet osmotic minipumps or by daily injections powerfully inhibited the growth of these tumors [28-301. The present study provides the first evidence for the significant inhibitory effect of bombesin antagonist RC-3095 on the growth of PC-82 human prostatic cancer line xenografted in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonist RC-3095 was highly active in vivo in rats, dogs, and cats in abolishing gastric and pancreatic secretion [45]. Potential oncological application of antagonist RC-3095 was revealed in our studies on pancreatic, colon, and mammary cancers, in which the administration of RC-3095 from Alzet osmotic minipumps or by daily injections powerfully inhibited the growth of these tumors [28-301. The present study provides the first evidence for the significant inhibitory effect of bombesin antagonist RC-3095 on the growth of PC-82 human prostatic cancer line xenografted in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…The total binding was found to be 8.79% with 88.3% specific binding. There was 'no displacement with any of the following: insulin, Substance P, [D-Trp6] LH-RH or GRP (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The displacement of labelled SS-14 by native SS-14 ( Fig.…”
Section: Receptor Assaysmentioning
confidence: 98%
“…These potent antagonists in nanomolar concentrations block GRP-stimulated amylase release from rat pancreatic acini, show strong binding affinity to Swiss 3T3 and H-346 SCLC cells and inhibit GRP-stimulated growth of thcsc cells in vitro (19,20). Their in vivo activity was also demonstrated in various systems (17,19).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, Göke et al , (1986) showed that chronic stimulation of endogenous CCK release by camostate also induces pancreatic hypertrophy and hyperplasia. Subsequent studies (Niederau et al , 1986; Wisner et al , 1988; Schmidt et al , 1989; Douglas et al , 1990; Konturek et al , 1991) have confirmed the initial observation and have shown that this effect is mediated through stimulation of CCK A ‐receptors.…”
Section: Discussionmentioning
confidence: 69%